Progression of aortic regurgitation following transcatheter closure of intracristal ventricular septal defects in children: a mid- to long-term follow-up study - Li, Qiuman; Zhang, Xu; Xu, Yukai; Zhou, Lingmei; Li, Junjie; Zhang, Zhiwei (Frontiers in Cardiovascular Medicine, 2023)
Background Early surgical closure is warranted to prevent aortic valve lesion and aortic regurgitation (AR) in intracristal ventricular septal defects (icVSDs). Experiences for transcatheter device closure of icVSDs are still limited. Our objectives are to investigate AR progression following transcatheter closure of icVSDs in children and to explore the risk factors for AR progression. Methods and results From January 2007 to December 2017, 50 children with icVSD who had successfully undergone transcatheter closure were enrolled. With 4.0 (interquartile range: 3.0–6.2) years of follow-up, AR progression was observed in 20% (10/50) of patients after icVSD occlusion, among which 16% (8/50) remained in mild level and 4% (2/50) evolved to moderate. None progressed to severe AR. Freedom from AR progression was 84.0%, 79.5%, and 79.5% at 1, 5, and 10 years of follow-up. A multivariate Cox proportional-hazards model revealed that x-ray exposure time [hazard ratio (HR): 1.11, 95% confidence interval (CI): 1.04–1.18, P = 0.001] and the ratio of pulmonary to systemic blood flows (HR: 3.38, 95% CI: 1.11–10.29, P = 0.032) were independent predictors for AR progression. Conclusions Our study suggested that transcatheter closure of icVSD in children is safe and feasible in mid- to long-term follow-up. No serious AR progression occurred after icVSD device closure. Greater left-to-right shunting and longer x-ray exposure time were both risk factors for AR progression.